Scaffold fabrication from drug loaded HNT reinforced polylactic acid by FDM for biomedical applications - Kokcu, Ilknur; Eryildiz, Meltem; Altan, Mirigul; Ertugrul, Melek Ipek; Odabas, Sedat (WILEY, 2023)
In this study, multifunctional polymer nanocomposite scaffolds were fabricated by the fused deposition method (FDM) for biomedical applications. First, halloysite nanotube reinforced (1-5 wt%) polylactic acid filaments were prepared by melt mixing process. For the selected compositions, HNT was loaded with metformin (MET) by electrostatic interactions. The characterization of the scaffolds was observed by Fourier transform infrared spectroscopy, X-ray photoelectron spectroscopy, differential scanning calorimetry, and thermogravimetric analysis. The morphology of the nanocomposite scaffolds was investigated by scanning electron microscope. Mechanical behavior of the scaffolds was determined by tensile, compression, and three-point flexural tests. It has been seen that 3%wt of HNT loading showed 124%, 145%, and 41% increments in tensile, compression, and three-point flexural strength of the scaffolds, respectively. In-vitro drug release and cell viability of the scaffolds were also examined. According to the cell viability result, a better cell proliferation regimen was achieved in all HNT-containing groups without any cytotoxicity effect. Also, approximately 50% of the total drug was released from the scaffolds at the end of 120 h. Finally, it has been seen that the developed scaffolds show promise for bone regeneration and replacement of bone.
Keywords: drug loading; FDM; halloysite nanotube; polylactic acid; scaffold; MECHANICAL-PROPERTIES; THERMAL-PROPERTIES; POLY(LACTIC ACID); BIOACTIVE GLASS; NANOCOMPOSITES; MORPHOLOGY; EXTRUSION; BEHAVIOR; RELEASE; Materials Science; Polymer Science